Soybean and casein hydrolysates induce grapevine immune responses and resistance against Plasmopara viticola - Lachhab, Nihed; Sanzani, Simona M.; Adrian, Marielle; Chiltz, Annick; Balacey, Suzanne; Boselli, Maurizio; Ippolito, Antonio; Poinssot, Benoit (Frontiers in Plant Science, 2014)
Plasmopara viticola, the causal agent of grapevine downy mildew, is one of the most devastating grape pathogen in Europe and North America. Although phytochemicals are used to control pathogen infections, the appearance of resistant strains and the concern for possible adverse effects on environment and human health are increasing the search for alternative strategies. In the present investigation, we successfully tested two protein hydrolysates from soybean (soy) and casein (cas) to trigger grapevine resistance against P. viticola. On Vitis vinifera cv. Marselan plants, the application of soy and cas reduced the infected leaf surface by 76 and 63%, as compared to the control, respectively. Since both hydrolysates might trigger the plant immunity, we investigated their ability to elicit grapevine defence responses. On grapevine cell suspensions, a different free cytosolic calcium signature was recorded for each hydrolysate, whereas a similar transient phosphorylation of two MAP kinases of 45 and 49 kDa was observed. These signalling events were followed by transcriptome reprogramming, including the up-regulation of defence genes encoding pathogenesis-related (PR) proteins and the stilbene synthase enzyme responsible for the biosynthesis of resveratrol, the main grapevine phytoalexin. Liquid chromatography analyses confirmed the production of resveratrol and its dimer metabolites, δ- and ε-viniferins. Overall, soy effects were more pronounced as compared to the cas one. Both hydrolysates proved to act as elicitors to enhance grapevine immunity against pathogen attack.